Mapping QTLs associated with Barley seed germination under normal and drought stress conditions - zeinab taghizadeh; hossein sabouri; Hossein Hosseini, Moghaddam; Fallahi Hossein Ali; Mahnaz Katouzi (علوم و فناوری بذر ایران, 2019)
Seed germination is a manifest characteristic of the standard germination test of a cultivated variety. In order to identify genomic regions associated with seed germination, 103 family of barley in F3 and their parents Badia and Kavir were cultivated in 2015-2016, under normal and drought stress conditions. Different traits including Plumule length, Radicle number, Cleoptil length, Radicle Dry weight, Plumule Dry weight and germination speed were measured. In this study, 28 pairs of microsatellite primers were used to determine the parental polymorphism. QTL analysis using composite interval mapping (CIM) for each trait in each environment for all studied traits. In general, twenty seven QTLs were detected for all traits. Total phenotypic variance explained by these QTLs varied from 8.6 to 37.3 percent. The highest LOD value for QTL controlling Radicle number (LOD=10.45) was obtained on chromosome 4 qNR-4a -15 in drought stress The results revealed that QTLs of Radicle number had desirable performance in all two environments. However, detected stable and cluster QTLs may be used in marker assisted selection (MAS) programs.